(untitled) (Cadernos Benjaminianos, 2019)
Resumo: Propõe-se uma reflexão cruzada entre Walter Benjamin e Robert Walser, a partir de suas micrografias. Dentre os muitos objetos que colecionou durante a vida, Benjamin tinha especial apreço por livros infantis, miniaturas e brinquedos. Esse interesse pelo diminuto também se manifestava na extrema pequenez de sua letra e no desejo de chegar a cem linhas numa folha de carta de tamanho convencional, feito conseguido por Walser, que escrevia microtextos com uma grafia minúscula e sobre quem o próprio Benjamin redigiu um curtíssimo ensaio em 1929. Se, por um lado, a letra miniaturizada de Benjamin e de Walser aponta para um gesto de escrita que parece cifrar o conteúdo do texto, por outro lado, a micrografia de ambos diz do interesse mútuo de se esconder nas malhas textuais através de um apequenamento do eu pela escrita. Pode-se, ainda, aproximar a miniaturização da letra de uma estreita vinculação com o universo da infância, seja pelos personagens crianças e fracassados presentes na obra de Walser; seja pelo protagonismo que a infância como Denkbild (imagem de pensamento) assume nos escritos de Benjamin. A partir dessas afinidades eletivas, o artigo procura mostrar a miniaturização como um procedimento de escrita de Benjamin e de Walser através de paralelos entre suas micrografias e de comentários analítico-especulativos de ensaios de Benjamin e de contos de Walser. Palavras-chave: Walter Benjamin; Robert Walser; escrita; miniaturização, infância. Abstract: The article proposes a cross-reflection between Walter Benjamin and Robert Walser and finds its first intersection in the micrographs produced by them. Among the many objects collected during his lifetime, Benjamin seems to have had a special appreciation for children’s books, miniatures and toys. This interest in small items was also manifested in the extreme smallness of his handwriting and in the desire to write one hundred lines in a conventional-size paper – this last one achieved by Walser, who wrote microtexts in a miniscule handwriting and was also the subject of a short essay Benjamin wrote in 1929. If, on the one hand, the miniaturized handwritings of both Benjamin and Walser point to a manner of writing that seems to encrypt the content of texts, on the other hand, the micrographies constructed by both men state a mutual interest in hiding amongst the textual mesh through the suppression of the self in writing. One can, still, liken the miniaturized handwriting with the universe of childhood, be it by the character of the child or the character of the so-called underdog (both present in the works of Walser) or by the protagonism that a childhood-as-Denkbird (image of thought) assumes in Benjamin’s work. Based on these elective affinities, the article seeks to show the miniaturization as a writing procedure employed by both Benjamin and Walser, and it will do so by establishing parallels between the micrographs of the latter and the analytical-speculative commentaries present in Benjamin’s essays and in Walser’s tales. Keywords: Walter Benjamin; Robert Walser; writing; miniaturization; childhood.